1984
DOI: 10.1104/pp.74.2.213
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Proline Analog l-Thiazolidine-4-carboxylic Acid on Proline Metabolism

Abstract: The effect of various proline analogs on proline oxidation in mitochondria isolated from etiolated barley (Hordeum vulgare) shoots was investigated. Ofthe analogs tested, only L-thiazolidine-4-carboxylic acid (T4C) was an effective inhibitor. T4C (1 millimolar) inhibited proline (10 millimolar) -dependent 02 uptake an average of 67%. T4C was also oxidized to some degree (12.9 nanoatoms oxygen per minute per milligram protein for 10 millimolar). The effect of T4C on the oxidation of other mitochondrial substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1
1

Year Published

1984
1984
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 9 publications
(19 reference statements)
1
23
1
1
Order By: Relevance
“…Different nucleotide specificities have also been reported for varieties of the same species; while P5C reductase from Hordeum vulgare var Augusta was most active with NADPH (9), the enzyme from H. vulgare var Larker preferred NADH over NADPH by a factor of at least threefold (4). Some of this discrepancy could be explained if two P5C reductases were present in plants as has already been suggested (4,17). However, no isozymes of P5C reductase were found in C. autotrophica or C. saccharophila.…”
Section: Pyndine Nucleotide Specificitymentioning
confidence: 95%
See 1 more Smart Citation
“…Different nucleotide specificities have also been reported for varieties of the same species; while P5C reductase from Hordeum vulgare var Augusta was most active with NADPH (9), the enzyme from H. vulgare var Larker preferred NADH over NADPH by a factor of at least threefold (4). Some of this discrepancy could be explained if two P5C reductases were present in plants as has already been suggested (4,17). However, no isozymes of P5C reductase were found in C. autotrophica or C. saccharophila.…”
Section: Pyndine Nucleotide Specificitymentioning
confidence: 95%
“…More recently, Treichel (23) showed that P5C reductase activity and substrate affinity increased with progressive adaptation to NaCl stress of cell suspension cultures of Mesembryanthemum nodiflorum. Cells grown in 400 mM NaCl showed nearly 4 times more activity of P5C reductase than cells cultivated 'Research supported by grant A6032 from the Natural Sciences and Engineering Research Council of Canada. 2Abbreviations: P5C, Av-pyrroline-5-carboxylate; ASW, artificial sea water; FPLC, fast protein liquid chromatography. 917 in the absence of NaCl.…”
mentioning
confidence: 99%
“…Extracts were centri-fuged at 16,000g for 10 min, and supernatants were used to determine ProDH activity in vitro by incubation in 0.15 M Na 2 CO 3 -HCl buffer (pH 10.3) with 1 mM NAD + and 20 mM L-Pro to monitor the NAD + reduction at 340 nm. The specificity of the enzymatic reaction was evaluated by incubation of samples with the ProDH inhibitor L-4-thiazolidine carboxylic acid (Elthon and Stewart, 1984 …”
Section: Prodh Analysismentioning
confidence: 99%
“…In previous studies (Mackenzie & Harris, 1957;Unger & DeMoss, 19663;Elthon & Stewart, 1984), oxidation of T4C by intact bacteria or mitochondria was measured manometrically as oxygen uptake. To determine if T4C degradation in E. coli is mediated by the membraneassociated enzyme proline dehydrogenase, a spectrophotometric assay for T4C catabolism was developed.…”
Section: Spectrophotometric Assay Of T4c Oxidation In Membrane Fractionsmentioning
confidence: 99%